Hot-cracking of high-alloyed steels evaluated by wedge rolling test - Schindler, I.; Suchanek, P.; Rusz, S.; Kubecka, P.; Sojka, J.; Heger, M.; Liska, M.; Hlisnikovsky, M. (Проблемы прочности, 2008)
We present a new methodology of determination of hot-cracking f metallic materials, which is based on laboratory application of the wedge rolling test and computer processing of the results obtained. The experiment was made with selected new types of high-alloyed free-cutting (ferritic and austenitic) steels. The initial specimens underwent an additional modification enabling easier development of cracks which consisted in milling out of the defined V-shaped notches on a side wall of a specimen. After taking specimens from the rolled material, we performed the metallographic analysis of microstructures by means of optical microscopy as well as a SEM analysis of the cracks. The resulting microstructure in the propagating crack vicinity was markedly influenced by this fracture. In the crack vicinity, a noticeable refinement of grains was observed due to the stress-induced recrystallization and occurrence of deformation zones that were pronounced by the rolled-out and stretched sulphides. As a rule, fractures were created by the ductile failure with visible pits, caused by tearing of sulphides from the material. Susceptibility of the studied steels to hot-cracking was evaluated and compared.